Studies on the synthesis of peptides containing dehydrovaline and dehydroisoleucine based on copper-mediated enamide formation - Gille, Franziska; Kirschning, Andreas (Beilstein Journal of Organic Chemistry, 2016)
The preparation of peptide fragments containing dehydrovaline and dehydroisoleucine moieties present in the antibiotic myxovalargin is reported. Peptide formation is based on a copper-mediated C–N cross-coupling protocol between an acyl amide and a peptidic vinyl iodide. The presence of a neighboring arginine in the vinyl iodide posed a challenge with respect to the choice of the protecting group and the reaction conditions. It was found that ornithine – a suitable precursor – is better suited than arginine for achieving good yields for the C–N cross-coupling reaction. The optimized conditions were utilized for the synthesis of peptides 32, 33, 39 and 40 containing a neighboring ornithine as well as for the tripeptide 44 containing dehydroisoleucine with the correct stereochemistry.
Keywords: catalysis; dehydroamino acids; Hartwig–Buchwald reaction; myxovalargin; peptides

(untitled) - Humphrey, J. M.; Chamberlin, A. R. (Chem. Rev., 1997)

Amino Acids, Peptides and Proteins in Organic Chemistry - Kazmaier, U. (Synthesis and Chemistry of α,β-Dehydroamino Acids, 2009)

(untitled) - Ley, S. V.; Priour, C.; Heusser, C. (Org. Lett., 2002)

(untitled) - Schmidt, U.; Lieberknecht, A.; Wild, J. (Synthesis, 1988)

(untitled) - Bonauer, C.; Walenzyk, T.; König, B. (Synthesis, 2006)

(untitled) - Ogawa, T.; Kiji, T.; Hayami, K.; Suzuki, H. (Chem. Lett., 1991)

(untitled) - Shen, R.; Porco, J. A., Jr (Org. Lett., 2000)

(untitled) - Shen, R.; Lin, C. T.; Bowman, E. J.; Bowman, B. J.; Porco, J. A., Jr (J. Am. Chem. Soc., 2003)

(untitled) - Jiang, L.; Job, G. E.; Klapars, A.; Buchwald, S. L. (Org. Lett., 2003)

(untitled) - Pan, X.; Cai, Q.; Ma, D. (Org. Lett., 2004)

(untitled) - Kuranaga, T.; Sesoko, Y.; Inoue, M. (Nat. Prod. Rep., 2014)

(untitled) - Evano, G.; Theunissen, C.; Pradal, A. (Nat. Prod. Rep., 2013)

(untitled) - Kuranaga, T.; Sesoko, Y.; Sakata, K.; Maeda, N.; Hayata, A.; Inoue, M. (J. Am. Chem. Soc., 2013)

(untitled) - Irschik, H.; Gerth, K.; Kemmer, T.; Steinmetz, H.; Reichenbach, H. (J. Antibiot., 1983)

(untitled) - Irschik, H.; Reichenbach, H. (J. Antibiot., 1985)

(untitled) - Huang, X.; Anderson, K. W.; Zim, D.; Jiang, L.; Klapars, A.; Buchwald, S. L. (J. Am. Chem. Soc., 2003)